PDF/A-3 solution for digital calibration certificates. (December 2021) - Boschung, Gregor; Wollensack, Michael; Zeier, Markus; Blaser, Cédric; Hof, Christian; Stathis, Manuel; Blattner, Peter; Stuker, Florian; Basic, Nina; Grasso Toro, Federico
Abstract: The digitalization of metrology poses a challenge to all members of the metrology community. We propose an approach for digital calibration certificates (DCCs) based on a PDF/A-3 solution that could be a stepping-stone towards the digitalization of metrological services. We present multiple applications of this approach by fulfilling discussed minimum requirements and satisfying needs from both customers and laboratories.